PEDAGOGICAL CONDITIONS OF PROFESSIONAL TRAINING COMPETENT PROFESSIONAL TEACHER - L.L. Sushentseva (Academy of Cognitive and Natural Sciences, 2008)
In the article an author describe the problem of propation competent teacher of the vocational training for the professional educational system.